2017
DOI: 10.1016/j.celrep.2016.12.069
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Approach Reveals MAVS Signaling in Myeloid Cells as Critical for Resistance to Ebola Virus in Murine Models of Infection

Abstract: SUMMARY The unprecedented 2013–16 outbreak of Ebola virus (EBOV) resulted in over 11,300 human deaths. Host resistance to RNA viruses requires RIG-I-like receptor (RLR) signaling through the adaptor protein, mitochondrial antiviral signaling (MAVS), but the role of RLR-MAVS in orchestrating anti-EBOV responses in vivo is not known. Here, we apply a systems approach to MAVS−/− mice infected with either wild-type or mouse-adapted EBOV. MAVS controlled EBOV replication through expression of IFNα, regulation of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Tilorone causes a rapid increase in the mitochondrial potential (after 30 minutes), which may reflect the activity of the direct downstream signaling partner of RIG-I called the mitochondrial antiviral signaling protein (MAVS) (43). The RLR signaling and the MAVS protein have been shown to be a critical mediator of viral replication in mice (44). In vitro binding data shows that tilorone can directly bind human RIG-I, though only weakly when the assay is performed in a simple buffer with no other cellular components (Fig.…”
Section: Initiallymentioning
confidence: 99%
“…Tilorone causes a rapid increase in the mitochondrial potential (after 30 minutes), which may reflect the activity of the direct downstream signaling partner of RIG-I called the mitochondrial antiviral signaling protein (MAVS) (43). The RLR signaling and the MAVS protein have been shown to be a critical mediator of viral replication in mice (44). In vitro binding data shows that tilorone can directly bind human RIG-I, though only weakly when the assay is performed in a simple buffer with no other cellular components (Fig.…”
Section: Initiallymentioning
confidence: 99%
“…Shed EBOV GP ectodomain, generated from virion‐ and cell‐associated GP that is cleaved with cell surface proteases, was able to activate uninfected macrophages in a TLR‐4 dependent manner resulting in cytokine production (i.e., TNF, IL‐1β, IL‐6, IL‐8, IL‐12p40, IL‐10) and up‐regulation of co‐stimulatory markers . Consistent with this, a number of studies demonstrated that purified EBOV GP, EBOV GP constructs or EBOV VLPs administered to monocytes, macrophages or DCs leads to significant production of proinflammatory cytokines, chemokines and type I interferon responses . Olejnik et al.…”
Section: Ebov Elicits Mϕ Immunopathologymentioning
confidence: 63%
“…The role of several signaling pathways was observed for some other RNA viruses, including VSV [12] or rotavirus [19]. In certain viral infections, however, including Ebola virus or rhinovirus infection, either MAVS or MyD88 signaling alone, respectively, was shown to be sufficient to induce efficient antiviral protection [20,21]. Interestingly, although TLR3/TRIF signaling was shown to be important in certain viral infections [11], it does not seem to be critical in NiV infection in mice.…”
Section: Discussionmentioning
confidence: 99%